THE REFLECTION OF THE POLITICAL LIFE AND STATE ADMINISTRATION PROCEDURES OF THE AGE OF THE SHAIBANIS IN THE BUKHARA KHANTY IN THE EUROPEAN WRITTEN SOURCES - Alimova Farida (Western European Studies, 2024)
In this artikle, based on the work of Antoni Jenkinson the author sheds light on the issues of state management in Bukhara Khanate in the 16 th century
Keywords: nomadic Uzbeks; Dashti Kipchak; Moscow trading company; metropolitane